STUDIES CONCERNING THE EVOLUTION OF THE LEADER APPROACH, PART OF THE COMMON AGRICULTURAL POLICY, AS A SUPPORT FOR SUSTAINABLE DEVELOPMENT OF THE RURAL AREA - Luxita Georgiana STAIC; Marius VLADU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article aims to analyze the evolution of the LEADER approach from the pilot project stage to the present. The article aims to the stages of the LEADER approach and their particularities from the timid beginnings of LEADER in Europe and emphasize the relevant aspects of this innovative approach: principles, eligible territory, added value. LEADER has emerged as a necessity of rural development policies regarding the objective of their interventions, interventions aimed at revitalizing rural areas and creating jobs. It follows the evolution of the relevant indicators of the LEADER approach in Europe and in Romania such: covered territorial area, allocated amounts. Also, some data are presented to highlight the LEADER financial allocation compared to the rest of the EAFRD budget allocated to that country. For the first stage LEADER the financial allocation was 442 million euros distributed to a number of 217 local action groups, the success of LEADER being proved over time by the increasing financial allocation, the covered area and the number of local action groups, respectively: 9,400 million euros and 2,784 LAGs in Europe in 2014 – 2020. In Romania, there are 239 LAGs that have financial allocation of 563.50 million euros and an eligible territory of 228,754 km2.